How to build a game for empirical bioethics research: the case of “Tracing Tomorrow" - Lyreskog, D; Pavarini, G; Lorimer, J; Jacobs, E; Bennett, V; Singh, I (Wiley, 2021)
It is becoming increasingly clear that the field of empirical bioethics requires methodological innovations that can keep up with the scale and pace of contemporary research in health and medicine. With that in mind we have recently argued for Design Bioethics – the use of purpose-built, engineered research tools that allow researchers to investigate moral decision-making in ways that are embodied and contextualised. In this paper, we outline the development, testing, and implementation of a novel prototype tool in the Design Bioethics Workshop – with each step illustrated with collected data. Titled ‘Tracing Tomorrow’ (www.tracingtomorrow.org), the tool is a narrative game to investigate young people’s values and preferences in the context of digital phenotyping for mental health. The process involved: (1) Working with young people to discover, validate and define the morally relevant cases or problems, (2) Building and testing the game concept in collaboration with relevant groups and game developers, (3) Developing prototypes that were tested and iterated in partnership with groups of young people and game developers, and (4) Disseminating the game to young people to collect data to investigate research questions. We argue that Design Bioethics yields tools that are relevant, representative, and meaningful to target populations, and provide improved data for bioethics analysis.